Synthetic Index to Measure the Quality of Employment in Micro and Small Enterprises in Ecuador - Basante-Garcés, José Luis (2022)
At a global level, employment is not only the engine of a country's economy, but it is also a right that all citizens have and that directly affects the living conditions of the active population. Every human being has the right to a decent quality of life to be able to cover their needs, both physiological, security, affiliation, recognition and self-realization, for which it is considered important to analyze not only the generation of employment but also the quality of employment. existing in micro and small businesses in the Ecuadorian context. The objective of this research is to establish an index that is capable of measuring the quality of employment of micro and small companies, it will be structured by multiple determinants, such as: type of contract, working hours, social security and income level. The methodology to be used will be a synthetic index created by Stefano Farné that has served as the basis for different studies in the region. Finally, with all the variables established, with their respective weights, an econometric model will be established that will measure the quality of employment in micro and small companies in Ecuador.